Two Additional Remarks on Conformism - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
Abstract This note offers two comments on the article “Social Influences towards Conformism in Economic Experiments” by Hargreaves Heap that is to appear in the Economics e-Journal. One relates to the concept of conformism, the other lines out some phenomena where an explicit recognition of group processes, such as conformism, may be analytically helpful.
urn:nbn:de:bvb:19-epub-18376-3
Keywords: C91; C92; D43; H41; J41; D1; 330; Conformism; relative income hypothesis; reference group behavior; social multiplier; social preferences; self-classification; group polarization